IoT based automation system for smart home - Tee, Kok Kian (2019)
Due to communications technology advancement, home automation system has grown in popularity. Smart Home (SH) is one of the Internet of Things (IoT) applications that allow the users to control and real time monitor the home appliances through internet connection. Most existing systems are not affordable for most users due to high cost and difficult in maintenance. In addition, the existing systems are either locally or remotely controlled. Last but not the least is the lack of user-friendly interface. To overcome these limitations, this project proposes a cost effective and hybrid (local and remote) IoT-based home automation system which monitors and controls home appliances easily and efficiently via a user-friendly interface using smartphones and/or laptops. The project aims at enhancing the design and fabrication of an existing SH prototype to utilizing the IoT technology. The proposed system will integrate both technologies; Wi-Fi for local control and the IoT for enabling remote control and monitoring via an IoT platform and check ubiquitously if something is happening. This allows the system support the independence of both mobile provider and user location. NodeMCU act as a microcontroller and WIFI as a communication protocol. The messages sent from the WI-FI connected microcontroller managed system can be received by the users on smartphone or computer from any distance by making sure that the electronic devices are connected to the internet. The software used to program the NodeMCU is the Arduino software (IDE). This software helps to write and upload the program into the chip in the microcontroller. The system then can merged to the switches and sensor of home appliances to prove efficient control. Several sensors will be attached to under controlled household appliances and placed throughout the home to track activities and events, and then send the sensed data wirelessly to a gateway. The system will be integrated with alert devices to detect any threats for safety and security purposes. The proposed system will be an enabler for easier, safer, and more comfortable life especially for elderly and disabled people.